The Influence of Local Primacy-Based Comic Media on Green Behaviour and Student Motivation - Baiq Herlia Rukmayanti; Baiq Muli Harisanti (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This research describes the results of implementing local primacy-based comic media in fostering green behaviour and student learning motivation. This study employed a pre-experimental design using the one-group pre-test post-test method. The research was conducted at SDN 1 Labuapi and SDN 1 Kuranji, West Lombok Regency. The measurement of green behaviour and student learning motivation used questionnaire sheets. The green behaviour questionnaire employed a Likert scale of three aspects, nine indicators, and fourteen statements with response options: score 1 = disagree, 2 = somewhat disagree, and 3 = agree, with reverse scoring for negative statements. The student motivation questionnaire adopted and modified a questionnaire consisting of four aspects: Choice of tasks, Effort, Persistence, and Self-confidence. Learning outcome data were analyzed, and the N-gain values were calculated and converted into 0.7 < g ≤ 1 (high), 0.3 < g ≤ 0.7 (medium), and g ≤ 0.3 (low). Finally, a t-test was conducted to determine the differences in student learning motivation and green behaviour between the two experimental classes. Implementing region-based comic media impacted green behaviour and elementary school student motivation (p < 0.05). Furthermore, the improvement in green behaviour for both experimental classes was categorized as a medium, while the increase in student motivation was categorized as low. Further analysis indicated no significant differences in student motivation and green behaviour between the two experimental schools. This could be attributed to the students' similar initial understanding in both experimental schools.